Management and Organizational Characteristics for Social Responsible Behavior of Small and Medium-Sized Business in Bulgaria - Slavova, Irena (Research Papers, 2018)
The main objective of the study is to reveal the nature and the main characteristics of the socially responsible behavior of small and medium-sized businesses in Bulgaria, based on the innovation diffusion theory and the results of an empirical survey. The identified degree of awareness, the relation between the perception characteristics of corporate social responsibility (benefits, motivation, complexity, compatibility) and making a decision to implement it, as well as the type of applied social initiatives show similarity to established practices in the existing literature.